The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.ppat.1009263
|View full text |Cite
|
Sign up to set email alerts
|

Endoribonuclease-mediated control of hns mRNA stability constitutes a key regulatory pathway for Salmonella Typhimurium pathogenicity island 1 expression

Abstract: Bacteria utilize endoribonuclease-mediated RNA processing and decay to rapidly adapt to environmental changes. Here, we report that the modulation of hns mRNA stability by the endoribonuclease RNase G plays a key role in Salmonella Typhimurium pathogenicity. We found that RNase G determines the half-life of hns mRNA by cleaving its 5′ untranslated region and that altering its cleavage sites by genome editing stabilizes hns mRNA, thus decreasing S. Typhimurium virulence in mice. Under anaerobic conditions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It was reported that the deletion of rraA resulted in reduced motility in V. vulnificus and Salmonella Typhimurium ( 12 , 31 ). However, no significant impact on motility was observed for V. alginolyticus .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the deletion of rraA resulted in reduced motility in V. vulnificus and Salmonella Typhimurium ( 12 , 31 ). However, no significant impact on motility was observed for V. alginolyticus .…”
Section: Discussionmentioning
confidence: 99%
“…Cas9-assisted editing in bacteria has been used to assess the phenotypic effects of individual point mutations (32) and of more extensive edits such as modification of ribosomes (33), introduction of genes encoding new metabolic pathways (34)(35)(36)(37)(38) and deletion of virulence genes (1,39). Additionally, creation of large mutant libraries has enabled screening of the effects of edits on antibiotic resistance (21) and essential gene functions (24,40).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, creation of large mutant libraries has enabled screening of the effects of edits on antibiotic resistance (21) and essential gene functions (24,40). While the introduction of desired edits is typically confirmed by Sanger sequencing, the genomes of edited strains are often not sequenced (1,3,32,(35)(36)(37)(38)(39). Thus, the possibility that edited cells might harbor unintended mutations elsewhere in the genome is often overlooked.…”
Section: Introductionmentioning
confidence: 99%